Latino Children's Body Mass Index at 2–3.5 Years Predicts Sympathetic Nervous System Activity at 5 Years - Alkon, Abbey (Mary Ann Liebert, Inc., 2014)
Background: To understand whether the relationship between young children's autonomic nervous system (ANS) responses predicted their BMI, or vice versa, the association between standardized BMI (zBMI) at 2, 3.5, and 5 years of age and ANS reactivity at 3.5–5 years of age, and whether zBMI predicts later ANS reactivity or whether early ANS reactivity predicts later zBMI, was studied. Methods: Low-income, primarily Latino children (n=112) were part of a larger cohort study of mothers recruited during early pregnancy. Study measures included maternal prenatal weight, children's health behaviors (i.e., time watching television, fast food consumption, and time playing outdoors), children's height and weight at 2, 3.5, and 5 years, and children's ANS reactivity at 3.5 and 5 years. ANS measures of sympathetic nervous system (i.e., pre-ejection period) and parasympathetic nervous system (i.e., respiratory sinus arrhythmia) activity were monitored during rest and four challenges. Reactivity was calculated as the difference between mean challenge response and rest. Structural equation models analyzed the relationship between children's zBMI at 2, 3.5, and 5 years and ANS reactivity at 3.5 and 5 years, adjusting for mother's BMI, children's behaviors, and changes in height. Results: There was no association between zBMI and ANS cross-sectionally. Children with high zBMI at 2 or 3.5 years or large zBMI increases from 2 to 3.5 years of age had decreased sympathetic activity at 5 years. Neither sympathetic nor parasympathetic reactivity at 3.5 years predicted later zBMI. Conclusions: Increased zBMI early in childhood may dampen young children's SNS responses later in life.